CRITICAL AND EFFECTIVE READING TO BUILD THE CHARACTERS AS ACTIVE READERS - Nina Suzanne (International Conference on Languages and Arts, 2014)
Basically, everyone already has its own character. However, the character can also be formed through habit and experience. As it is explained by Lickona (2013:72), a good character consists of knowing, desiring, and doing the good─mind habit, heart habit, and action habit. Consciously or not, people have a variety of character instilled in him through activities done daily, such as reading habit.  Good readers do not necessarily accept or reject what they read, but must be critically analyzed the reading through various critical reading techniques, namely making inference, distinguishing facts from opinion, identifying tone, purpose, and bias. In addition, active readers should apply different reading skills in each reading activity based on the purpose and reading texts chosen, so that the activity can take place more effectively and helpful. The reaction of readers to reading materials by selecting appropriate reading skills and is followed by careful analysis can encourage the formation of good character in him. Active readers are critical, sensitive, carefully, objective, flexible, responsible, prudent, effective, disciplined, and have a high curiosity towards reading.   Key words: Active Readers, Character building, Critical and Effective Reading